China's aid & soft power in Africa the case of education & training - King, Kenneth (Boydell & Brewer James Currey, 2013)
China?s increasing role as an education and Human Capital donor in Africa, and the significance of this both economically and politically.
Includes bibliographical references (p. [215]-228) and index.
Keywords: Education --Africa --Finance.